Interannual drought length governs dissolved organic carbon dynamics in blackwater rivers of the western upper Suwannee River basin. Issue 4 (10th December 2013) - Mehring, A. S.; Lowrance, R. R.; Helton, A. M.; Pringle, C. M.; Thompson, A.; Bosch, D. D.; Vellidis, G.
Abstract [1] The Little River (LR) in southern Georgia, U.S., has experienced lengthening droughts since monitoring began in 1972. We evaluated the impacts of drought on riverine carbon cycling using a 9 year data set of dissolved organic carbon (DOC) coupled with laboratory experiments in the LR, as well as long‐term data sets in three additional rivers within the Suwannee River basin. Longer drought periods reduced downstream DOC export but also led to higher DOC concentrations in the following hydroperiod. Within a hydroperiod, DOC concentration was positively correlated with temperature and negatively correlated with river discharge but also negatively correlated with total discharge during the previous hydroperiod. Among hydroperiods, DOC concentration was more strongly correlated with antecedent hydrological conditions than with current hydrological conditions across broad spatial scales: in three additional rivers within the Suwannee River basin (Alapaha, Withlacoochee, and Okapilco) and in headwater and downstream reaches of the LR. Microbial DOC consumption and CO2 production were elevated when DOC concentration was high. Despite dramatic hydrologic changes, DOC composition appeared stable, with optical analyses suggesting that LR DOC is primarily composed of three terrestrial humic‐like fluorescence groups. If the current climatic trend of intensifying droughts, elevated temperatures and decreased discharge continue, our results suggest the net effect may be for a more localized riverine carbon cycle with reduced downstream transport of DOC, but higher local mineralization rates due to elevated DOC concentrations.